1995
DOI: 10.1007/bf01556372
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of a transient new coherent condition of matter formed in high-energy hadronic collisions

Abstract: We investigate the dynamical possibility for the formation of a transient new coherent condition of matter in high-energy hadronic collisions. The coherent bosonic amplitude is characterized by a non-zero momentum and is sustained by P -wave interactions of quasi-pions in a dense fermionic medium.We make quantitative estimates of several essential properties: the condensate momentum and the fermionic density, the size of the coherent amplitude and the negative energy density contributed by the condensate, a ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Turning to the models exploiting collective behavior of radiation sources (let us call them collective models for brevity), it is interesting to note that in Barshay's model of a transient new coherent condition of matter [65][66][67][68], proposed for the explanation of the anomalous soft photon production in hadronic beam experiments [9][10][11], the soft pho-ton radiation enhancement appears also due to an explicitly non-linear feature of the model, but the radiation itself is coherent and the enhancement occurs due to a constructive interference of radiation sources [65].…”
Section: General Remarksmentioning
confidence: 99%
“…Turning to the models exploiting collective behavior of radiation sources (let us call them collective models for brevity), it is interesting to note that in Barshay's model of a transient new coherent condition of matter [65][66][67][68], proposed for the explanation of the anomalous soft photon production in hadronic beam experiments [9][10][11], the soft pho-ton radiation enhancement appears also due to an explicitly non-linear feature of the model, but the radiation itself is coherent and the enhancement occurs due to a constructive interference of radiation sources [65].…”
Section: General Remarksmentioning
confidence: 99%
“…In the system, the energies can be very small on the usual scale of m π , down to E γ of the order of 1/T ≃ 6 MeV with a bremsstrahlung-like spectrum [29], [28]. We have estimated [28] that the level of anomalous emission can reach several times the level of the bremsstrahlung from incoming and outgoing charged hadrons. Since the latter is at the level [12] of about 2 %, this corresponds to a soft photon occurring in of the order of 10 % of inelastic collisions.…”
mentioning
confidence: 94%
“…If charged currents exist during the evolution of the coherent system, then it has been shown that soft photons will be emitted [29]. In the system, the energies can be very small on the usual scale of m π , down to E γ of the order of 1/T ≃ 6 MeV with a bremsstrahlung-like spectrum [29], [28]. We have estimated [28] that the level of anomalous emission can reach several times the level of the bremsstrahlung from incoming and outgoing charged hadrons.…”
mentioning
confidence: 99%
See 2 more Smart Citations